Adherence to treatment with denosumab, its efficacy and safety in women with postmenopausal osteoporosis in clinical practice - N. V. Toroptsova; O. A. Nikitinskaya; T. A. Korotkova; N. V. Demin (Современная ревматология)
Adherence to treatment with antiosteoporotic drugs is one of the most important factors contributing to their efficacy during longterm therapy. The adherence is assessed by two main lines: firstly, how long a drug is taken and, secondly, whether its dosage regimen is adhered.Subjects and methods. The paper gives the data of a 12-month prospective follow-up study of 40 women with postmenopausal osteoporosis (OP) who initiated treatment with the biological agent denosumab.Results and discussion. After the 12-month follow-up, the significant bone mineral density increase was 4.9% in the lumbar spine, 3.2% in the femoral neck, and 3.0% in the total hip. The previous administration of other antiosteoporotic drugs did not lower the efficiency of denosumab therapy. There were no cases of osteoporotic fractures during 1-year follow-up. 95% of the patients received two denosumab injections (an annual cycle); moreover, 90% of the women were noted to adhere to the dosage regimen. Age, marital status, level of education, time taken to reach the clinic, parental femoral fractures, a history of fractures, duration of OP, and previous therapy had no impact on treatment adherence during 12 months.Conclusion. The one-year prospective follow-up study of the outpatients demonstrated that denosumab was an effective and safe agent for the treatment of patients with postmenopausal OP and its dosage regimen implying its rare subcutaneous administration (twice yearly) ensured the high patient adherence to therapy.